Glycerophosphodiester Phosphodiesterase Identified as Non-Reliable Serological Marker for Borrelia miyamotoi Disease - Reiter, Michael (Microorganisms, 2020)
The relapsing fever group Borrelia miyamotoi is an emerging tick-borne pathogen. Diagnosis of infection is currently mainly based on serological methods detecting antibodies against B. miyamotoi glycerophosphodiester phosphodiesterase (GlpQ). Here, we scrutinized the reliability of GlpQ as a diagnostic marker and compared the seroprevalence in different study populations and by applying various immunoblotting methods. Antibodies were detected in the sera of 7/53 hunters and in 1/11 sera of Lyme neuroborreliosis patients. Furthermore, 17/74 sera of persons with high concentrations of anti-Borrelia burgdorferi sensu lato (α-Bbsl) antibodies reacted strongly with B. miyamotoi GlpQ in immunoblots. The B. miyamotoi GlpQ seroprevalence was 7/50 in α-Bbsl negative persons. In healthy blood donors from commercial suppliers and from the Austrian Red Cross, seroprevalences were 5/14 and 10/35, respectively. Strikingly, two B. miyamotoi PCR-positive cases from Austria had negative GlpQ serology, indicating poor sensitivity. Finally, when we analyzed sera of dogs, we found α-B. miyamotoi GlpQ antibody seroprevalence in tick-free dogs (n = 10) and in tick-exposed dogs (n = 19) with 2/10 and 8/19, respectively. Thus, our results indicate that GlpQ-based B. miyamotoi serology holds neither specificity nor sensitivity.